Ecology and theology together within African Pentecostals worship liturgy - Sande, Nomatter (Acta theologica, 2024)
The African Pentecostal pneumatological experiences and the hesitancy to engage with the "other-worldly" (earth-based/earthly) matters have contributed to the slow uptake to contribute to the ecological crisis. An intentional, comprehensive, practical approach is needed to alleviate the ecological crisis. For the ecological strategies to be effective, they should blend into the churchs spiritual life, such as worship. The starting point is to identify and amplify any ecological notions that the church uses consciously or unconsciously. This study uses qualitative data to explore how hymnal worship songs construct and dialogue ecotheological notions. It concludes that bringing ecology and theology together within the church worship liturgy is an appropriate strategy for churches to contribute to the ecological crisis.